(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Menopause is a period of transition every woman passes at the age 45-55 and with several challenges and pressure on marriages. This study centres on the influence of interpersonal communication on husbands’ attitude towards menopausal wives in Obukpa Town, Enugu State. Three research question were formulated and a total of 10 participants were purposively selected from the population of 260 to participate in a focus group discussion because their wives over 50 years of age. It was found that a majority of men do not know much about menopause and did not even know when their wives got to that stage. It was equally found that due to this limited information, the level of support menopausal women get from their husbands was small, however, it did not greatly affect their marriage satisfaction. Men marry for several reason and can remain with their wives due to good moments they had shared in the past, but this affects the woman’s quality of life.